Bentuk-Bentuk Perampingan dan Harmonisasi Regulasi - Ibnu Sina Chandranegara (Fakultas Hukum Universitas Islam Indonesia, 2019)
Since the reformation era, the number of laws and regulations has continued to increase. In the period 2000-2017 there have been 35,901 regulations. The highest number is Regional Regulation (Perda), which has reached 14,225 Perda. Followed by Ministerial Regulation (Permen) as many as 11,873 regulations. While on the third place, sit 3,163 non-ministerial regulations. This research has the main objective of finding the best alternative policy to simplify and rearrange the regulations as an agenda for the law reform. This is a normative juridical research. The data used are secondary data that includes primary and secondary legal material in the form of relevant laws and regulations used as samples as examples of regulations that are out of sync, incoherent, and potentially overlapping. The results concluded that the arrangement of the regulations can be carried out on three sectors, which are the simplification of regulations, reconceptualization in order to understand the regulatory requirements, and creating synergies amongst the the law-makers.